BRIEF REVIEW OF CONCEPTS ENGINEERING OF HADFIELD STEEL PROPERTIES AND APPLICATIONS - Teixeira, Ricardo Luiz Perez; Silva, Priscilla Chantal Duarte; Junior, Anibal Ferreira Pinto (Seven Editora, 2024)
Hadfield manganese austenitic steel, characterized by high strength and exceptional abrasion resistance, is widely employed in industries such as mining, cement, and railways. Its composition, typically 1–1.4 wt% carbon and 10–14 wt% manganese, ensures superior wear resistance and ductility under stress. The steel’s remarkable work-hardening ability, attributed to dislocation accumulation and twinning, enhances its mechanical properties. However, challenges such as carbide precipitation at grain boundaries lead to embrittlement and reduced weldability, necessitating precise control during casting and heat treatment. Key methods such as solutionizing, rapid quenching, and heat treatment at temperatures ranging from 950°C to 1000°C are essential to dissolve carbides and improve mechanical properties. The steel’s machinability is hindered by its high strain-hardening capacity and low thermal conductivity, resulting in rapid tool wear. To address this, hot machining and advanced cutting tools, such as carbide and cubic boron nitride, are employed to improve performance. Despite these challenges, Hadfield steel remains the material of choice for wear applications due to its unique combination of toughness and work-hardening properties. Ongoing research aims to optimize its performance, particularly in high-abrasion and impact conditions. The integration of modern techniques like additive manufacturing and cryogenic treatments has been highlighted as potential solutions to further enhance its properties. DOI: https://doi.org/10.56238/sevened2024.037-087